Projectively Flat Finsler Space with A \(r\)-th Series \((α,β)\)-Metric - S.T., Aveesh; Narasimhamurthy, S.K.; Ramesh, G. (Journal of Informatics and Mathematical Sciences, 2015)
The \((α,β)\)-metric is a Finsler metric which is constructed from a Riemannian metric and a differential 1-form \(β\), it has been sometimes treated In theoretical physics. The condition for a Finsler space with an \((α,β)\)-metric \(L(α,β)\) to be projectively flat was given by matsumoto. The present paper, We discuss the \(r\)-th series \((α, β)\)-metric to be projectively flat on the basis of Matsumoto’s results.